Influence of Non-fibrous Carbohydrate and Degradable Intake protein and Ruminal Fermentation ,Nutrien Digestion and performance of Local Sheep - AR, Efka; Suwandyastuti, SNO; Iriyanti, Ning (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2001)
The objective of current study was to evaluate the impact dietary non-fibrous carbohydrate ( NFC) and ruminally degradable intake protein (DIP) concentration have on ruminal fermentation , nutrient digestion and performance of local sheep. The animal had a mean of Â liveweight 19.80 Â±1.55 kg. four diets ,arranged in a 2x2 factorial ,were formulated to contain either 40 or 50 % NFC and 50 or 60 % of dietary crude protein as DIP .dietary DM contained 25 % Indonesian field grass and 75 % concentrate. Solvent âextracted or formaldehyd Â 2 % -treated soybean meal were used to alter DIP and corn or soybean hulls to alter NFC level. Percentage ofÂ energy and NDF digestion was similar ( p<0,01) as DIP level decreased in the diets. The soybean hulls was fermentable and total VFA concentration in the rumen increased ( p<0.01), but N-NH3 concentration was decreased ( p<0.01) as DIP level decreased in the diets. Daily live weight gain ( 146.29Â±25.84 g) and body composition ( fat, water , protein and mineral) was similar ( p<0.05) among diets. The preponderance ruminal fermentation ,nutrient digestion and performance of local sheeps did not be improved by sincronization of energy and nitrogen release but may more likely be limited by either energy or nitrogen alone. (Animal Production 3(2): 53-61 (2001)Key Word : Carbohydrate, protein, rumen fermentation, nutrients digestion and performance